Facile one-pot fabrication of a silica gel-supported chiral phase-transfer catalyst—N-(2-cyanobenzyl)-O(9)-allyl-cinchonidinium salt1. Issue 4 (24th April 2015) - Feng, Dandan; Xu, Jinghan; Wan, Jingwei; Xie, Bing; Ma, Xuebing
<x xml:space="preserve">Abstract</x> A novel silica gel-supported cinchona alkaloid-based PTC catalyst was prepared by one-pot synthesis for the first time. Excellent enantioselectivities (72.0–96.9% ee) and 80–96% yields in enantioselective α-alkylation were achieved without significant loss in the catalytic performance for five runs.